Activation of Stat3 Sequence-specific DNA Binding and Transcription by p300/CREB-binding Protein-mediated Acetylation - Wang, Rui; Cherukuri, Pratima; Luo, Jianyuan (The Journal of biological chemistry, 2005)
Signal transducers and activators of transcription (Stat) belong to a family of latent cytoplasmic factors that can be activated by tyrosine phosphorylation by members of the Jak tyrosine kinase family in response to a variety of cytokines and growth factors. Activated Stats form dimers and translocate into nucleus to induce expression of critical genes essential for normal cellular events. Here we report for the first time that Stat3 can be modified by acetylation both in vivo and in vitro. A major site of Stat3 that is acetylated by its coactivator, p300/CREB-binding protein (CBP), resides in the C-terminal transcriptional activation domain at lysine 685. Furthermore, the acetylation of Stat3 can stimulate its sequence-specific DNA binding ability and transactivation activity. Inhibition of histone deacetylase activity in cells results in increased Stat3 nuclear localization. These observations clearly indicate a novel mechanism for Stat3 activation in mammalian cells.